Treating perinatal asphyxia with theophylline at birth helps to reduce the severity of renal dysfunction in term neonates. (6th June 2016) - Raina, Alok; Pandita, Aakash; Harish, Rekha; Yachha, Monika; Jamwal, Ashu
Abstract: Aim: Perinatal asphyxia is a common neonatal problem and contributes significantly to neonatal morbidity and mortality. This study was designed to determine whether theophylline could prevent or ameliorate renal dysfunction in term neonates with perinatal asphyxia. Methods: We randomised 159 severely asphyxiated term newborns to receive a single dose of 5 mg/kg intravenous theophylline (n = 78) or a placebo (n = 81) during the first hour of life. The infant's 24‐hour fluid intake, urine volume, serum creatinine, creatinine clearance and sodium excretion were recorded during days one, three and five of life, starting 12 hours after the theophylline or placebo infusion. Results: Neonates in the theophylline group had lower serum creatinine levels (0.83 ± 0.35 versus 1.47 ± 0.61; p = 0.00) and higher endogenous creatinine clearance (32.16 ± 16.34 versus 17.73 ± 7.92; p = 0.00) than the placebo group. Severe renal dysfunction, namely acute kidney injury, was present in 36 (15%) of the neonates in the theophylline group versus 117 (48%) in the placebo group (p < 0.01). Conclusion: A single dose of intravenous theophylline administered to term neonates with perinatal asphyxia within the first hour of life significantly decreased serum creatinine levels and significantly increased creatinine clearance.